Identification and validation of T cell senescence-related prognostic genes in gastric carcinoma and investigation of their potential regulatory mechanisms - Jing Liu; Huiyu Wang; Fang Huang; Zhiqiang Hang; Pan Xu; Runjie Wang; Junying Xu (Discover Oncology)
Abstract Objective This study aimed to identify prognostic genes associated with immunosenescence in gastric carcinoma (GC) and to elucidate their mechanisms to provide new ideas for the clinical treatment of GC. Methods According to single cell data, clustering and annotation were conducted to acquire key cells. Then, differentially expressed genes (DEGs) in key cells (KC-DEGs) and TCGA-GC (GC-DEGs) were obtained, and took their intersection with CS-RGs to obtain candidate genes. Afterwards, prognostic genes were identified by regression analyses. Following this, the risk model was constructed, and the high-risk and low-risk groups were obtained. Next, a nomogram based on independent prognostic factors was constructed for predicting survival in GC. Finally, to further explore the mechanisms associated with the risk groups, immune microenvironment analysis was performed. Results T cells were used as key cells. Subsequently, AXL, PIM1, STK40, CXCL1, IFNG and SERPINE1 were identified as prognostic genes. The risk model and nomogram had favourable predictive capability in survival of GC patients. Surprisingly, 17 differential immune cells had higher levels of infiltration in the high-risk group, a result that was further confirmed in tumor purity. Notably, there was mostly a positive correlation between them and prognostic genes. Then, both tumor mutation burden (TMB) and microsatellite instability (MSI) were lower in the high-risk group, suggested the high-risk group might be associated with lower treatment benefit. Conclusion 6 prognostic genes were identified, providing novel concepts in prognosis and therapy for GC.